Cecocolic Intussusception in Adult Caused by Acute Appendicitis - Jeonghyun Kang; Kang Young Lee; Seung-Kook Sohn (Case Reports in Surgery)
Intussusception in adult is rare. The etiology is different from that of childhood. The most common cause of intussusception in adult is known as malignancy. When dealing with adult intussusception, surgical resection is usually warranted for correct diagnosis and proper treatment. This is a case report of cecocolic intussusception caused by an acute appendicitis in adult. The causes of cecocolic intussusception were reported as appendiceal adenocarcinoma, appendiceal mucocele, appendiceal adenoma, or idiopathic. Although this patient underwent laparoscopic right hemicolectomy under suspicion of malignancy at cecum base, final pathologic diagnosis revealed only acute appendicitis. Thus, the present case emphasizes the importance of prior thorough examinations including colonoscopy when we encounter this rare kind of intussusception in adult.